2023
DOI: 10.1039/d2ra06104j
|View full text |Cite
|
Sign up to set email alerts
|

Magnetically separable triazine-based Cu(ii)–vitamin B5 complex in nitromethane toward efficient heterogeneous cyanation reaction of aryl halides

Abstract: An efficient heterogeneous copper catalyst was developed by supporting copper acetate on magnetically separable triazine–vitamin B5. Its catalytic efficiency was evaluated in the cyanation of aryl halides with nitromethane as a non-toxic and cost-effective cyanating source.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
(32 reference statements)
0
3
0
Order By: Relevance
“…In addition, a comparison of reaction efficiencies between aryl iodides and aryl bromides reveals the former's superiority, attributed to the weaker C–I bond in contrast to the C–Br bond. 14,27…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a comparison of reaction efficiencies between aryl iodides and aryl bromides reveals the former's superiority, attributed to the weaker C–I bond in contrast to the C–Br bond. 14,27…”
Section: Resultsmentioning
confidence: 99%
“…In addition, a comparison of reaction efficiencies between aryl iodides and aryl bromides reveals the former's superiority, attributed to the weaker C-I bond in contrast to the C-Br bond. 14,27 Additionally, in the utilization of the Pd/CoFe 2 O 4 @ACT nanoparticles, it was observed that electron-rich or electron-decient substitutions were not pivotal factors affecting product yields. Furthermore, analysis from Table 8 indicates that aryl halides with O-substitution (2d and 2h) yielded lower results than their counterparts with P-substitution (2b and 2e), suggesting a hindrance effect as a contributing factor.…”
Section: @Act Catalyst In Cyanation Reactionmentioning
confidence: 99%
See 1 more Smart Citation